Ischaemic myelopathy associated with cocaine: clinical, neurophysiological, and neuroradiological features. Issue 4 (1st October 1997) - Di Lazzaro, V; Restuccia, D; Oliviero, A; Profice, P; Nardone, R; Valeriani, M; Colosimo, C; Tartaglione, T; Della Corte, F; Pennisi, M A; Tonali, P
Abstract : Two patients with spinal infarction and one patient with the previously unreported complication of spinal transient ischaemic attack associated with cocaine misuse are reported. Spinal MRI documented an infarction in the territory of the anterior spinal artery in the first two patients and was completely normal in the patient with a transient ischaemic attack. Motor evoked potentials were abnormal in all three patients.